Effectiveness of Health Promotion Strategies on Dengue Hemorrhagic Fever Prevention and Control: A Literature Review - Martiningsih, Ika; Trisnowati, Heni; Sulistyawati, Sulistyawati (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a mosquito-borne infectious disease whose prevention and control depend largely on effective health promotion to influence community behavior. Objective: This study aims to review the effectiveness of health promotion strategies in improving public literacy for DHF prevention and control. Methods: A literature review was conducted by analyzing five relevant articles published between 2020–2024 from Google Scholar, PubMed, Research Gate, and GARUDA databases. The selected articles were descriptively analyzed to evaluate the implementation and outcomes of health promotion strategies. Results: The review shows that health promotion strategies integrating advocacy, social support, and community empowerment are effective in reducing the incidence of DHF when implemented through coordinated cross-sector collaboration. Active community participation strengthens behavioral change and program sustainability. Nevertheless, several barriers persist, including limited political commitment, inadequate monitoring systems, and insufficient resources, which reduce the effectiveness of these strategies. The findings emphasize that health promotion must be adaptive, participatory, and supported by clear policy frameworks to maximize impact. Conclusion: Strengthening collaboration across sectors, ensuring adequate resources, and tailoring health promotion to local community needs are essential to achieving sustainable and effective dengue prevention and control in Indonesia.